EFFECT OF FOLIAR APPLICATION OF ZINK AND SALICYLIC ACID ON VEGETATIVE GROWTH AND YIELD CHARACTERISTICS OF HALAWANI GRAPE CULTIVAR (Vitis vinifera L.) - Al-Atrushy, Sh. M. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
THis investigation aimed to study the effect of foliar application with zinc alone or in combination with salicylic acid on vegetative growth, yield, physical and chemical properties of Halawani grapevine cultivar during two successive seasons (2017 and 2018). Zinc was used at concentration of 2 and 4 g.L-1 in a chelated form and salicylic acid at concentration of (50, 100 and 150 mg. L-1) in addition to control treatment for each of them. The result obtained proved that all parameters such as leaf area, total chlorophyll, number and weight of cluster, yield, berries size and weight, as soon as TSS, total sugar, juice percentage and density, β-carotenes, Zn, N. proline content of leaves were increased significantly as compared with control, while total acidity and total phenols were decreased by all treatments as compared with control. Furthermore, combination between high concentration of zinc and salicylic acid improved all parameters in comparison with the control.